The Pragmatic Argumentation of Discourse Markers in English Academic Writing: A Corpus-Based Analysis - Al-Baidhani, Mareb Mohammed Sangoor (ANGLISTICUM. Journal of the Association-Institute for English Language and American Studies, 2018)
Academic writing is a key skill for success in academic life, particularly for graduate students of a foreign language. The importance of writing to academic culture, practice, and knowledge building has led to a great deal of research in many fields, including rhetoric and composition, linguistics, applied linguistics, and English for Academic Purposes (EAP). Often, studies and research investigating academic writing are motivated by the need to inform the learning of writing to native and non-native English-speaking students, through both descriptions of professional academic writing as well as through comparisons of novice writer (native and non-native English-speaking) and expert production. However, while learning about academic writing to better inform teaching content and practices is an important aim, Bazerman (1994, P. 10) points out that understanding language use in the disciplines also helps us to use language more effectively, can guide writers and editors as they work with contributor texts, and helps provide non-specialist readers with access to the discourse of the disciplines. Thus, describing and understanding patterns and pragmatic of argumentation of language use in academic writing allows us to understand the disciplinary cultures and practices that they embody. This is why many linguists and scholars have long been fascinated with the language of academia, particularly in the form of written texts. This interest has developed and expanded over the past few decades, in part due to the premise that much can be learned about disciplinary practices and cultures by examining academic writing: the primary means of the transmission of knowledge in academic fields. Keywords: discourse markers, university essay, L1-L2 writers, coherence-based approach, language use in academic writing, etc.